Singular Ideals of Ternary Semirings (European Journal of Pure and Applied Mathematics, 2012)
The notion of singular ideal in a ternary semiring is introduced. The notions of singular ternary semirings and nonsingular ternary semirings are also defined. Some properties of singular ideals in ternary semirings are given. Our results obtained can be used to study some radical classes related to singular ideals.